ABCD1 gene mutation in an Italian family with X-linkedadrenoleukodystrophy: case series. (18th May 2021) - Mohn, Angelika; Polidori, Nella; Aiello, Chiara; Rizzo, Cristiano; Giannini, Cosimo; Chiarelli, Francesco; Cappa, Marco
Abstract : Summary: Adrenoleukodystrophy is a peroxisomal X-linked recessive disease caused by mutations in the ABCD1 gene, located on the X-chromosome (Xq28). Gene mutations in patient with adrenoleukodystrophy induce metabolic alterations characterized by impaired peroxisomal beta-oxidation and accumulation of very long chain fatty acid (VLCFA) in plasma and in all tissues. Although nutritional intervention associated with a various mixture of oil prevents the accumulation of VLCFA, to date no causal treatment is available. Therefore, haematopoietic stem cell transplantation (HSCT) and gene therapy are allowed only for very early stages of cerebral forms diagnosed during childhood.We reported a case series describing five family members affected by X-linked adrenoleukodystrophy caused by a novel mutation of the ABCD1 gene. Particularly, three brothers were affected while the sister and mother carried the mutation of the ABCD1 gene. In this family, the disease was diagnosed at different ages and with different clinical pictures highlighting the wide range of phenotypes related to this novel mutation. In addition, these characteristics stress the relevant role of early diagnosis to properly set a patient-based follow-up. Learning points: We report a novel mutation in the ABCD1 gene documented in a family group associated to an X-ALD possible Addison only phenotype. All patients present just Addison disease but with different phenotypes despite the presence of the same mutations. Further follow-up is necessary to complete discuss the clinical development. The diagnosis of ALD needs to be included in the differential diagnosis in all patients with idiopathic PAI through accurate evaluation of VLCFA concentrations and genetic confirmation testing. Early diagnosis of neurological manifestation is important in order to refer timely to HSCT. Further follow-up of these family members is necessary to characterize the final phenotype associated with this new mutation.